2009
DOI: 10.1002/stem.49
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Mesenchymal Stem Cell Aging: Involvement of Antioxidant Defense and Actin Cytoskeleton

Abstract: Progenitor cells such as mesenchymal stem cells (MSCs) have elicited great hopes for therapeutic augmentation of physiological regeneration processes, e.g., for bone fracture healing. However, regeneration potential decreases with age, which raises questions about the efficiency of autologous approaches in elderly patients. To elucidate the mechanisms and cellular consequences of aging, the functional and proteomic changes in MSCs derived from young and old Sprague-Dawley rats were studied concurrently. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(172 citation statements)
references
References 50 publications
(63 reference statements)
7
156
1
Order By: Relevance
“…This however is still controversial. Other studies indicate that oxidative stress correlates with MSC senescence (145,146). These different results may be consequent to different ROS inductors, and consequently, different levels of ROS production and enviromental contributing factors envolved.…”
Section: Anti-oxidative Factorsmentioning
confidence: 99%
“…This however is still controversial. Other studies indicate that oxidative stress correlates with MSC senescence (145,146). These different results may be consequent to different ROS inductors, and consequently, different levels of ROS production and enviromental contributing factors envolved.…”
Section: Anti-oxidative Factorsmentioning
confidence: 99%
“…Adult stem cells present in mammalian organs are essential for tissue generation, maintenance and injury repair throughout adult life. Similar to other somatic cells, adult stem cells experience lifelong exposure to intrinsic and extrinsic factors, throughout the lifetime of the organism, which lead to an age-associated decline in their number and function (Janzen et al, 2006;Kasper et al, 2009;Rao and Mattson, 2001;Trosko, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[17]. Kasper and colleagues compared the proteomic profile of young and old MSCs under osteogenic differentiation conditions and they ascribed the changed differentiating property of aged MSCs to the altered anti-oxidant defense and cytoskeleton dynamics [18]. Our group also found that the expression of peroxiredoxin-2, a member of the anti-oxidant system, declined during aging in the interstitial fluid of bone marrow [19].…”
Section: Proteomic Analysis Of Bone Marrow Agingmentioning
confidence: 79%